2021
DOI: 10.1177/14779714211049261
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining Adult Education and Training Participation by Education, Literacy, Gender, and Race/Ethnicity in the U.S.

Abstract: This study examined the associations between adult education and training (AET) participation, educational attainment, literacy skills, gender, and race/ethnicity among the U.S. adult population aged 25 to 65 years old (n = 5,450). Given the socioeconomic advancements of women and racial/ethnic minorities in the last few decades, including higher educational attainment, increased labor force participation, and greater income, and as new data becomes available, it is important to re-examine AET participation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…These barriers to AET participation are embedded in the specific socioeconomic contexts (Desjardins, 2015). Consistent with findings in existing scholarly works, Punksungka et al (2021) demonstrated that higher levels of educational attainment and income, which indicate greater socioeconomic status, are strongly associated with adults’ participation in any form of AET.…”
Section: Literature Reviewsupporting
confidence: 87%
See 3 more Smart Citations
“…These barriers to AET participation are embedded in the specific socioeconomic contexts (Desjardins, 2015). Consistent with findings in existing scholarly works, Punksungka et al (2021) demonstrated that higher levels of educational attainment and income, which indicate greater socioeconomic status, are strongly associated with adults’ participation in any form of AET.…”
Section: Literature Reviewsupporting
confidence: 87%
“…Similarly, while some studies suggest that older workers benefit from AET activities, others have found that older age is associated with lower AET participation or negative attitudes toward it (Roosmaa & Saar, 2017. It is widely recognized that individuals with higher human capital tend to seek additional knowledge and skills (Boeren et al, 2010). For instance, Ioannidou and Parma's (2022) study demonstrated that highly educated workers were more likely to engage in AET practices, reaffirming that higher educational attainment enhances the likelihood of subsequent learning participation among adult workers (Punksungka et al, 2021;Yamashita et al, 2019). Additionally, income can serve as a significant driver and extrinsic reward for participating in LLL (Tikkanen & Nissinen, 2018).…”
Section: Key Drivers Of Aet Participationmentioning
confidence: 96%
See 2 more Smart Citations
“…Researchers have noted the importance of work-place education (Larsen, 2022) and neighbourhood learning activities (Ollis, Starr, Ryan, Angwin, Harrison, 2017;Olis, et al, 2018). Relevant results have been obtained by researchers when examining and evaluating experiences in various countries: in United Kingdom (Kersh, Laczik, 2021), in Spain (Alfageme, Seguí-Cosme, Monteagudo-Cáceres, 2023), in Australia (Ollis, Starr, Ryan, Harrison, 2018), in USA (Punksungka, et al, 2022;Yamashita, Smith, Sahoo, Cummins, 2022), in South Africa (Mayombe, 2016), in Latvia , in China (Zhang, Perkins, 2023), where researchers have pointed out several innovative approaches. All indicated research results have confirmed the relevance of life-long education.…”
Section: Literature Reviewmentioning
confidence: 99%